Multivariate analyzes in red bean genotypes in the Cerrado-Pantanal ecotone (Research, Society and Development, 2021)
Common bean (Phaseolus vulgaris, L.) is the most cultivated species among the other species of the genus Phaseolus. The roxo type is among the commercial groups of common bean cultivated in Brazil. The objective of this work was to evaluate the agronomic performance of ten genotypes of roxo beans in the cerrado-pantanal ecótono region. The experiment was carried out at the State University of Mato Grosso do Sul, in the municipality of Aquidauana. The design adopted was in randomized blocks with three replications. The ten genotypes used are part of the national network of Cultivation and Use Value (VCU) tests developed by Embrapa – National Rice and Bean Research Center. The insertion height of the first pod (AIV) was evaluated; number of pods per plant (NVP); number of grains per pod (NGV); mass of one hundred grains (MCG); productivity (PROD). As for the statistical analyses, multivariate variance analyses, canonical variables and cluster analysis were processed using the Rbio software. In the analysis of canonical variables, it is observed that the first two variables explain more than 80% of the total variation contained in the original data set. The dendrogram divided the roxo bean genotypes into 4 groups, and productivity was the variable with the greatest influence, consequently, of the most intense contribution to the separation of the groups, followed by the mass of one hundred grains. The genotypes CNFRx 16353, CNFRx 16340 and CNFR 16932 presented the highest averages for the productivity variable.